Diseño de un plan de marketing para fomentar el desarrollo turístico del cantón Quevedo, Parroquia San Carlos año 2022 - Bajaña Vera, Víctor Hugo (2022)
The objective of this research was to design a marketing plan to promote tourism development in the parish of San Carlos; and in this way contribute to the improvement of the tourism vision of the parish, as well as to promote the growth and socioeconomic development of its inhabitants and the canton in general. It was detected that the San Carlos parish has tourist attractions and activities to be developed as well as sites that are not yet promoted as such but that would contribute significantly to tourism in the sector. In the marketing plan different strategies and forms of tourism promotion are proposed, which will allow the timely performance for commercial activities to the inhabitants, tending another approach to economic growth, in addition to promoting the parish of San Carlos through the different media established by the results mentioned in the survey which allowed to know the opinions of each of the people surveyed in order to promote timely and effective development of tourism, having a greater scope with the approval of individuals to the parish.